Influennce of the Roles of the Csos, Headteachers and Deputy Headteachers in Supervision of Curriculum Implementation in Class Four in Public Primary Schools in Rongo Sub-County Kenya - Ochieng, Joshua Olela; ogogo, Collins; Odera, Florence (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2019)
Supervision of teaching and learning in public primary schools in one of the most important functions of the Ministry of Education in Kenya. The ministry appoints the Quality Assurance and Standards Officers to monitor the quality of Education in schools. The Teachers Service Commission (TSC) also appoints the Curriculum Support Officers (CSOs) to monitor the quality of teaching and learning in schools. The main work of those two from the Ministry of Education and the Teachers Service Commission is to supervise the actual teaching and learning in Public Primary School. However, in recent years instructional supervision seems not to have been given a great deal of attention because the academic performance in schools and especially  in class four which is a transition class  from lower primary to upper primary has been very low in Rongo Sub-county.Few research studies have been carried out or conducted towards the dismal or poor performance of class four in Public Primary Schools in Rongo Sub-county. This study was uncured on General System theory by Von Bettalafy 1956. The study was guided by one objective that states: The influence of the roles of the supervisors in supervision of curriculum implementation in class four in public primary schools in Rongo Sub-county. The study adopted a descriptive survey design. The purpose of the study was to investigate the influence of the supervisors’ roles in the supervision of curriculum implementation in class four in public primary schools in Rongo Sub-County. The larger population was 603 whereby 74 were headteachers, 80 deputy headteachers, 444 class four teachers and 5 C.S.O. A sample size of 72 head teachers, 78 deputy headteachers, 133 class four teachers and 5 CSO (Curriculum Support Officers). Saturation sampling was used on head teachers, deputy head teacher and CSO, while random sampling was used on class four teachers because the number was more. Data was collected by the use of questionnaires for deputy head teachers and class four teacher and in-depth interview scheduled was used to collect data from CSO and head teachers. The data collected was analyzed through the use of descriptive statistics and according to themes.  From the study it emerged that the roles of the supervisors in the supervision of curriculum implementation has a great influence in the implementation of curriculum. It was also established that the supervisors does not give attentions to class four being especial class of transition from lower Primary to upper primary. They rarely supervise the teachers handling class four and they even do not check the pupil’s books. The CSO major in the lower classes for the programme of TUSOME and EGMA which are new methods of teaching reading and new mathematics. The study therefore recommended that the supervisors give attention to class four being that it’s a class where there is change on medium of instruction from the language of the catchment to English and Kiswahili.